PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SINAR NIAGA SEJAHTERA CABANG TASIKMALAYA - Setia Rachmanda, Yudi; Riswandi, Dede; Agustian, Aldy; Muhammad Nur Ihsan, Adi (JURNAL EKONOMI PERJUANGAN, 2024)
The purpose of this study is to: 1). Knowing the organizational commitment at PT. Sinar Niaga Sejahtera Tasikmalaya Branch. 2). Knowing the performance of employees at PT. Sinar Niaga Sejahtera Tasikmalaya Branch. 3). Knowing the influence of organizational commitment to employee performance at PT. Sinar Niaga Sejahtera Tasikmalaya Branch. The research method used in this study is descriptive and verification methods. Data collection techniques are carried out through field research and literature studies. Data analysis techniques are carried out through the analysis of the Correlation Coefficient to find the value of "r" and analysis of the Coefficient of Determination (KD) to calculate the amount of organizational commitment to employee performance. Whereas to test the hypothesis the "t" test is used. The results showed that organizational commitment at PT. Sinar Niaga Sejahtera Tasikmalaya Branch belongs to the very good category with a score of 145 upholding tolerance in working and adhering to the norms prevailing in the agency. Employee performance at PT. Sinar Niaga Sejahtera Tasikmalayater Branch includes a very good category with a score of 142 which is supported by an indicator of the quality and quantity of its work. The influence of organizational commitment to employee performance at PT. Sinar Niaga Sejahtera Tasikmalaya Branch is 73.78 and is supported by calculated values (9.633)> t table (2.04), then Ho is rejected and Ha is accepted. This means that organizational commitment has a significant influence on employee performance. Keywords: Organizational Commitment and Employee Performance